ANALISIS ANGGARAN DAN REALISASI BELANJA OPERASI PADA RUMAH SAKIT UMUM DAERAH BAGAS WARAS KLATEN - Anugerah Wati, Alisa Arum; Budiningsih, Benedicta (Jurnal Pendidikan Ekonomi dan Akuntansi, 2023)
Budget analysis and realization of operational expenses are crucial in hospital financial management. The purpose of this research is to measure the effectiveness and accuracy of the budget. Hospital data is collected and compared, revealing variations due to fluctuations in medical, operational costs, and technological developments. These variations have the potential to impact the financial performance of the hospital, such as inefficient cash management and potential budget deficits.This analysis aims to enhance monitoring and controlling variable costs, effective negotiations with suppliers, and diversification of revenue sources. Overall, the analysis of budget and realization of operational expenses in hospitals becomes a crucial step in maintaining financial balance, operational sustainability, and financial stability to provide quality healthcare services.Keywords: budget, realization, operational expenses